An educational test of learning potential assessment with Spanish-speaking youth - Budoff, Milton; Corman, Louise; Gimon, Alex (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The learning potential (LP) procedure represents an alternative method o f measuring the general ability o f Spanish-speaking students who tend to score low on traditional IQ tests. Post-teaching scores on an electricity curriculum unit test were used as criteria to compare the relative predictive power o f LP and IQ measures for Spanish-speaking students. Subjects were administered the Raven LP procedure, the Semantic Test o f Intelligence, the WISC Performance Scale in Spanish, and the WISC Vocabulary Subtest in Spanish and English. Before and after participation in an electricity unit, subjects took the electricity unit evaluation instrument. Post-training Raven LP scores significantly predicted performance on the minimally verbal symbolic level o f the electricity instrument. IQ scores were not positively related to post-teaching electricity scores. The LP procedure resulted in increased levels o f performance on a reasoning task